Casting a New Light on a Long Shadow: Saskatchewan Aboriginal High School Students Talk About What Helps and Hinders their Learning - Stelmach, Bonnie; Kovach, Margaret; Steeves, Larry (Alberta Journal of Educational Research, 2017)
What do teachers do (or not do) that makes you want to go to school? A team of Saskatchewan researchers asked Saskatchewan Aboriginal high school students this question about the aspects of instructional practice that helps and hinders their learning. While responses pointed to several aspects, teacher relational instincts and capacities were the most influential in school engagement for this group of Aboriginal students. Students in this study described three relational capacities of effective teachers: a) empathetic responsiveness to the student as whole being, b) the degree to which teacher disposition influenced the relational dynamic with students, and c) teachers’ responsiveness to the full context of the student’s life (including a sensibility of the student’s Indigenous culture). Through a case study process, focus group interviews were conducted in six Saskatchewan schools. The study included 75 Aboriginal high school students from six schools (urban, rural, provincial, and First Nations band schools) in Saskatchewan, Canada. The qualitative case study research design was informed by Indigenous principles, and the theoretical lens employed in the analysis relied predominately upon an Indigenous theoretical perspective, as articulated by Smith and Perkins (as cited in Kovach, 2014). The findings point to the teaching attributes of relationality, responsibility, and understanding of contextuality identified within an Indigenous theoretical framework as influential in fostering engaged learning environments for this group of Aboriginal high school students. Que font, ou ne font pas, les enseignants pour vous donner envie d’aller à l’école? Une équipe de chercheurs de la Saskatchewan ont posé cette question à des élèves autochtones au secondaire pour connaitre les aspects de la pratique pédagogique qui aident ou qui nuisent à leur apprentissage. Les réponses ont dévoilé plusieurs aspects, mais ce groupe d’élèves autochtones a indiqué que les instincts relationnels et les capacités des enseignants étaient les facteurs les plus influents dans leur engagement scolaire. Les élèves qui ont participé à cette étude ont décrit trois capacités relationnelles d’enseignants efficaces : a) leur réceptivité emphatique face aux élèves comme êtres entiers, b) la mesure dans laquelle le caractère de l’enseignant influençait la dynamique relationnelle avec les élèves et c) la réactivité des enseignants devant tout le contexte de la vie des élèves (y compris une sensibilité à la culture autochtone des élèves). Suivant un processus d’étude de cas, des entrevues ont eu lieu auprès de groupes de discussion dans six écoles en Saskatchewan. L’étude a impliqué 75 élèves au secondaire dans des écoles en milieu urbain et rural ainsi que des écoles de bande en Saskatchewan, au Canada. Le plan de recherche de cette étude qualitative de cas tenait compte de principes autochtones et la perspective théorique de l’analyse reposait largement sur une optique autochtone, telle que formulée par Smith et Perkins (citée dans Kovach, 2014). Les résultats indiquent que les caractéristiques de l’enseignement portant sur la relationnalité, la responsabilité et la compréhension de la contextualité telles qu’identifiées dans un cadre théorique autochtone jouent un rôle influent dans la promotion de milieux d’apprentissage actifs pour ce groupe d’élèves autochtones au secondaire.